(untitled) (Global Journal of Management and Business Research, 2020)
The study focuses on building the relationship between leadership roles and employee motivation among the kindergarten staff. Purposively, 50 participants have been taken considering from 20 kindergartens. Through a questionnaire, primary data has been gathered. The motivation multifactor questionnaire style has been used because of finding a broader view of the leadership impacts. Data has been analyzing by using the SPSS-23 version. A statistical tool like factor test, percentile has been used to show the relationship between motivation and leadership.